Peroxisome Proliferator-Activated Receptor-γ (PPAR-γ) Ligands: Novel Pharmacological Agents in the Treatment of Ischemia Reperfusion Injury - Giaginis, Costas; Tsourouflis, Gerasimos; Theocharis, Stamatios (Current Molecular Medicine, 2008)
Peroxisome proliferator-activated receptor-γ (PPAR-γ) ligands constitute important insulin sensitizers that have already been used for the treatment of human metabolic disorders, exerting also pleiotropic effects on inflammatory related diseases and cancer. Ischemia-reperfusion injury that is mainly associated with organ transplantation constitutes a serious complication with a great relevance in clinical practice. Accumulating experimental data have recently revealed that natural and synthetic PPAR-γ ligands exert beneficial effects against ischemia-reperfusion injury. The present review summarizes the available information on the role of PPAR-γ ligands in ischemia-reperfusion injury amongst the different organ systems. Taking into consideration the data so far, PPAR-γ ligands seem to represent potential therapeutic agents in the aim to reduce or even prevent injury associated with ischemia-reperfusion.
Keywords: inflammatory